2021
DOI: 10.1186/s12884-021-03590-2
|View full text |Cite
|
Sign up to set email alerts
|

“The kind of support that matters to exclusive breastfeeding” a qualitative study

Abstract: Background Worldwide, only 41 % of infants are exclusively breastfed for the first six months while South Africa has an alarming figure of only 12 %. First-time mothers are inexperienced in the initiation and maintenance of exclusive breastfeeding, hence a need for support. Data on forms and quality of exclusive breastfeeding support as experienced by first-time mothers is minimal. The study explored the exclusive breastfeeding support available to first-time mothers in the Buffalo City Metro, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…Family provides mothers the values and beliefs in breastfeeding practices [33]. This different finding might happen because mothers are able to decide which family supports they should accept or reject, especially for the supports that mothers considered harmful to the breastfeeding practices and maintaining exclusive breastfeeding [39].…”
Section: Discussionmentioning
confidence: 99%
“…Family provides mothers the values and beliefs in breastfeeding practices [33]. This different finding might happen because mothers are able to decide which family supports they should accept or reject, especially for the supports that mothers considered harmful to the breastfeeding practices and maintaining exclusive breastfeeding [39].…”
Section: Discussionmentioning
confidence: 99%
“…A review on breastfeeding among overweight and obese mothers found that these group of mothers are embarrassed to breastfeed in public because of the fear of exposing their body to others (Chang et al 2020). A study in Australia among breastfeeding mothers also reported that mothers often feel uncomfortable to breastfeed in public as they constantly need to avoid male gazing at them or people coming to see the baby while they are breastfeeding (Sheehan et al 2019). Hence, they often cover up and this led to them feeling scared of suffocating their child or afraid that their child is not being fed properly.…”
Section: Stigma Of Public Breastfeedingmentioning
confidence: 99%
“…Hence, they often cover up and this led to them feeling scared of suffocating their child or afraid that their child is not being fed properly. This discomfort remains a barrier in many countries in which social norm include them to cover themselves up properly if they breastfeed in public (Coomson & Aryeetey 2018;Sheehan et al 2019). It is important to create awareness among public and breastfeeding mothers in order to provide a comfortable environment for mothers to breastfeed to support breastfeeding.…”
Section: Stigma Of Public Breastfeedingmentioning
confidence: 99%
“…When social networking is applied to breastfeeding practices, nurses have been found to provide instrumental or practical support during breastfeeding initiation, while family members, friends, and community members provide support for the maintenance of EBF ( Theodorah & Mc’Deline, 2021 ). Among adolescent mothers, health professional support has been viewed as the most important factor influencing EBF at 6 months, while family conflict can create barriers to receiving positive support ( Nuampa et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%